ANALISIS STRATEGI BERSAING PADA RAMAYANA DEPARTMENT STORE PANAM SQUARE DI KOTA PEKANBARU - Alrijal Rizqa; Zulkarnain '; Tengku Firli Musfar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research held in Ramayana Department Store Panam Square in Pekanbaru City. Pekanbaru is a city that has a high consumption patterns, especially in fashion. This can be seen with the establishment of many department stores in Pekanbaru. One of them is Ramayana Department Store Pekanbaru. The purpose of this research is to know strategy Ramayana Department Store Panam Square Pekanbaru and know the effort Ramayana Department Store Panam Square Pekanbaru in improving competitive advantage. Variables used are internal factors (strengths and weaknesses) of the company and external factors (opportunities and threats) of the company. The population in this research is visitors Ramayana Department Store and Ramayana Department Store Manager. This research is a qualitative reasearch using qualitative descriptive method using collection techniques such as questionnaires, observations, documentations and interviews. This research used SWOT analysis. The results showed that the Ramayana Department Store Panam Square Pekanbaru has SO highest scores so that strategies can be used are as follows; expand market share, product development, product diversification and cooperation with various parties. Based on the Cartesius diagram, Ramayana Department Store Panam Square Pekanbaru is the position of Growth. The strategy used is the strategy of vertical integration.Keywords: Swot Analysis, Competitive Strategy, and Panam Square